Six sigma approach to real time cast in-situ slab concreting process improvement - Niaraki, Seyed Ali Mousavi (2010)
The best way of construction processes improvement is by problem solving approaches. Before problems start to emerge in construction phases. In accordance to experiencing in real time problem solving approaches in other industries processes this study suggest that its time to go toward other industries experiences in real time problem solving. Proposing check sheet for real time problem solving within Six Sigma by; Identifying problem’s root causes and taking preventive actions before facing problem during construction phase, is main target of this study. This study were conducted as project experience and data gathering from interview with related experts. For achieving this goal, study adopting cast in-situ slab concreting quality improvement. Finding root causes of plastic crack in cast in-situ slab concreting and eliminating them in first place by applying Six Sigma tools and techniques.